Improving the sexual activity and reproduction of female zebrafish with high testosterone levels - Congcong Liu (Nature Portfolio, 2021)
Abstract High levels of testosterone cause clinical symptoms in female reproduction and possibly, alterations in sexuality. Yet, the underlying mechanisms remain to be examined. Here, we report a study that investigates the effects of testosterone in follicle development and sexual mating using zebrafish models. We developed an acute zebrafish model with high testosterone levels by exposing young female zebrafish to testosterone dissolved in swimming water. After given a high concentration of testosterone treatment (e.g., 100 ng/ml), the fish showed hallmark pathological symptoms similar to those displayed in patients with polycystic ovary syndrome (PCOS), such as follicular growth-arrest, rare ovulation, ovary enlargement, decrease in reproduction, and down regulation of the expression of some PCOS susceptible genes, such as Tox3. These fish are referred to as the PCOS fish. By monitoring mating-like swimming behaviors, we measured the sexual activity of PCOS zebrafish. In general, the PCOS fish showed no desire to interact with males. As a consequence, their mating rate was decreased as compared to control animals. The sexuality levels of PCOS fish, however, could be improved after short periods of rearing in conditions that lack of males. After only 3 days of rearing alone, the PCOS fish showed an increase in sexuality levels and displayed characteristic swimming patterns for mating. After 30 days of separation from males, not only the sexual activity, but also the mating rate was improved in the PCOS fish. Together, the data suggests that zebrafish can serve as a new type of research model to further develop strategies for the treatment of reproductive disorders, such as those related to PCOS.